Новий скарб бронзових виробів з Коровії на Буковині - Ільків, Микола (Наші книги, 2008)
New bronze hoard from Koroviia in Bukovyna
Keywords: Late Bronze Age; bronze deposit; axe with disc and spine; sickles; bracelets; ingots; celts